Cardiac Energy Metabolism: A Potential Novel Therapeutic Target in the Treatment of Ischemic Heart Diseases - Abo Alrob, Osama (Jordan Journal of Pharmaceutical Sciences, 2017)
Despite decades of research, ischemic heart diseases (IHD) remain a major health problem in Jordan andworldwide. Ischemia is associated with serious and deleterious perturbations in biochemical, and functionalcharacteristics of the heart. During ischemia, the heart increased it is reliance on glycolysis as an ultimate sourcefor ATP production. However, fatty acid β-oxidation rates significantly increased at reperfusion. The metabolicdysregulation negatively impact both cardiac function and efficiency. Current treatment approaches of IHD mostlyfocus on increasing oxygen supply (e.g. thrombolytic agents) or decreasing oxygen demand (e.g. beta-blockers).However, therapeutic interventions aiming at improving cardiac efficiency of oxygen utilization have not gainedenough interest. In this review, this review focused on the metabolic pathways of fatty acid and glucose oxidation,as well as the metabolic phenotype of the ischemic heart. Furthermore, this review will discuss the mechanisms ofmetabolic modulators and how they can improve cardiac function in ischemia-reperfusion condition.